Dural spread from metastatic prostate cancer. Issue 4 (27th April 2021) - Peters, Niamh; Zemeer, Mohammed Zeeshan Zeeshan; Waters, Conor; Bambury, Richard
Abstract : A 59-year-old man with a known breast cancer type 1 gene mutation and a 2-year history of metastatic prostate cancer to bone and lymph nodes presented with a sudden onset of thunderclap headache, photophobia and a left sided facial droop. He was being treated at the time with the poly ADP ribose polymerase inhibitor Rucaparib. Of note, 6 weeks prior to this presentation, he had been diagnosed with malignant spinal cord compression at T3–T6, he underwent an emergency decompressive laminectomy and had received palliative postoperative radiotherapy. An urgent CT brain revealed dural metastases from his prostate cancer, with extensive oedema and midline shift. He underwent palliative whole brain radiotherapy but died 2 weeks later.